Potential and Actual soil losses assessment in Abjubeha, Sudan using USLE, RS and GIS analyses - Elgubshawi, Abdelmoneim A; Doka, Elabbas M. A; Suliman, Mahgoub (IJRDO - Journal of Business Management, 2017)
The natural and human induced effect on landscape changes in study area were analyzed. Aster image was used to classify landscape by supervised classification. Grain Size Index (GSI) was applied as indicator of the vulnerability level of topsoil to the erosion. Erosion risk assessment at sub-regional level was measured using modern digital techniques and the well-known Universal Soil Loss Equation (USLE). According to the result the area is subdivided into very low, low, moderate, high and severe erosion rates. The annual soil loss is greater than one tonne per hectare, at an averag of 1.23t/ha/year across the most of stuy area. Set of maps of study area were produced for different erosion rates. Subtle different between the actual (human induced) and potential (natural) erosion rate was recognized. The effect of individual soil erosion factors on erosion events as well as the erosion rate at different location within the study area were measured. The impact of landuse practice on erosion could not be fully undertaken due to a lack of spatial information